Identification of Malaria Receptive Areas to Support Elimination Maintenance in Gunungkidul District, Indonesia, 2023 - Handika, Denis Oxy; Utama, Muhamad Imam; Ananda, Dwi Rizki; Sukoco, Sidig Hery; Ahmad, Riris Andono (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: The Gunungkidul District in Indonesia achieved malaria elimination status in 2014; however, the risk of reintroduction remains due to environmental suitability and population mobility. This study aimed to identify malaria-receptive areas in Gunungkidul District through spatial and environmental analyses to support the strategic maintenance of malaria elimination.Methods: A descriptive observational study was conducted using secondary data from a vector survey conducted in October 2023 across 18 sub-districts. Geographic Information System (GIS) mapping and larval habitat index (LHI) calculations were used to identify potential Anopheles breeding sites. Climate data from 2020 to 2023 were analyzed to assess environmental receptivity.Result: Rivers were the most common breeding sites for Anopheles mosquitoes (59.41%), followed by lakes and springs. Gedangsari and Karangmojo sub-districts showed the highest larval habitat indices, indicating localized malaria receptivity in these areas. Climatic factors, such as high rainfall and humidity during the wet season, support year-round mosquito breeding. In 2023, four imported malaria cases were reported, underscoring the district's continued vulnerability.Conclusion : Spatial identification of malaria-receptive areas provides operational evidence to support the maintenance of the elimination status in the Gunungkidul District. Targeted surveillance and vector control in high-risk sub-districts, along with a rapid response to imported cases, are essential to prevent malaria re-establishment.